2008
DOI: 10.1529/biophysj.107.117473
|View full text |Cite
|
Sign up to set email alerts
|

Packaging of a Polymer by a Viral Capsid: The Interplay between Polymer Length and Capsid Size

Abstract: We report a study of the in vitro self-assembly of virus-like particles formed by the capsid protein of cowpea chlorotic mottle virus and the anionic polymer poly(styrene sulfonate) (PSS) for five molecular masses ranging from 400 kDa to 3.4 MDa. The goal is to explore the effect on capsid size of the competition between the preferred curvature of the protein and the molecular mass of the packaged cargo. The capsid size distribution for each polymer was unimodal, but two distinct sizes were observed: 22 nm for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
249
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(274 citation statements)
references
References 47 publications
21
249
0
Order By: Relevance
“…9 These have been compared to socalled "monster" structures that were found in in vitro studies of the assembly of turnip crinkle virus and capsid protein around the viral RNA. 10 12 correspond to Caspar-Klug structures with T ) 1, 3, 4, and 7; a so-called pseudo-Caspar-Klug structure with T ) 2 is also known. 13 The relative diameters of the capsids are related to their T numbers by the expression because the capsid surface area is proportional to T (and D 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…9 These have been compared to socalled "monster" structures that were found in in vitro studies of the assembly of turnip crinkle virus and capsid protein around the viral RNA. 10 12 correspond to Caspar-Klug structures with T ) 1, 3, 4, and 7; a so-called pseudo-Caspar-Klug structure with T ) 2 is also known. 13 The relative diameters of the capsids are related to their T numbers by the expression because the capsid surface area is proportional to T (and D 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…49,50 Examples include Flock house virus, which has a charge ratio of 1.4, and Brome mosaic virus, which ranges from 1.56 to 1.79 depending on the RNA fragment being encapsidated. Consistent with the electrostatic interaction driving assembly, previous work also showed that deletions of the basic residues in the CP results in reduced packaging of viral RNA.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The thermodynamic framework developed in this study should be useful for interpreting results from experimental studies of in vitro assembly of viruses and virus-like particles (22)(23)(24)(25)(26), as well as for the design of viral vectors for gene therapy, where, in addition to minimizing toxicity, a major goal is to successfully deliver the appropriate amount of therapeutic gene (27). More generally, because the presence of charged macromolecules in cells is ubiquitous, we expect the associated Donnan effects, much like the well known crowding effects (28), to significantly influence a wide range of biomacromolecular behaviors and cellular processes.…”
Section: Discussionmentioning
confidence: 99%